2019
DOI: 10.1002/oby.22584
|View full text |Cite
|
Sign up to set email alerts
|

Brown Adipocytes Secrete GDF15 in Response to Thermogenic Activation

Abstract: Objective Transcriptomic analysis of gene expression in brown adipose tissue (BAT) from mice in response to cold revealed strong induction of growth and differentiation factor 15 (GDF15). This study aimed to characterize GDF15 as a brown adipokine released in response to thermogenic activation and to determine its target functions. Methods GDF15 expression was measured in adipose tissues from mice in response to physiological and pharmacological modulators of thermogenesis. Brown and beige cell cultures were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 37 publications
2
40
0
Order By: Relevance
“…It has been reported that brown adipocytes are able to dampen the inflammatory responses in macrophages (Dowal et al 2017). We have confirmed that the conditioned medium from brown adipocyte cultures represses the pro-inflammatory activity of M1-activated macrophages (Cereijo et al 2018, Campderros et al 2019. However, identifying the molecular actors involved in the signalling from brown/ beige adipocyte to immune cells has unveiled a complex scenario.…”
Section: Immune Cells Novel Targets Of Batokines: the Chemokine C-x-supporting
confidence: 63%
See 1 more Smart Citation
“…It has been reported that brown adipocytes are able to dampen the inflammatory responses in macrophages (Dowal et al 2017). We have confirmed that the conditioned medium from brown adipocyte cultures represses the pro-inflammatory activity of M1-activated macrophages (Cereijo et al 2018, Campderros et al 2019. However, identifying the molecular actors involved in the signalling from brown/ beige adipocyte to immune cells has unveiled a complex scenario.…”
Section: Immune Cells Novel Targets Of Batokines: the Chemokine C-x-supporting
confidence: 63%
“…Recently, GDF15 has been reported to exert anorexigenic effects through its action at the brainstem and to contribute towards controlling the energy balance (Breit et al 2017. GDF15 is intensely secreted by brown fat upon exposure to cold conditions and by brown adipocytes after noradrenergic stimulation (Verdeguer et al 2015, Campderros et al 2019 and exerts mostly autocrine effects on macrophages, tuning down their pro-inflammatory responses (Campderros et al 2019). Whether these signalling capacities of brown adipokines towards immune cells are restricted to the local cross-talk between immune cells and adipocytes at adipose depots or have consequences on the systemic immune status of the organism are challenging possibilities that remain to be ascertained in further researches.…”
Section: Immune Cells Novel Targets Of Batokines: the Chemokine C-x-mentioning
confidence: 99%
“…Brown adipose tissue also secretes hormones called batokines. Several researchers have studied the hormones released when adipose tissues are browned [11,[25][26][27][28]. For example, fibroblast growth factor 21 (FGF21) is a secreted factor induced by noradrenergic cAMP-mediated mechanisms in brown adipocytes [26].…”
Section: Discussionmentioning
confidence: 99%
“…FGF21 increases the expression of PGC-1α and UCP1 in adipocytes and promotes thermogenesis [11]. In addition, growth and differentiation factor 15 (GDF15) is secreted from brown and beige adipocytes that undergo noradrenergic, cAMP-mediated thermogenic activation [27]. This targets macrophages and downregulates the expression of proinflammatory genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation